Recent Advancement in Deepfakes Generation and Detection Tools: A Review - Drishty Chaudhary (International Journal of Medical Toxicology and Legal Medicine, 2024)
Deepfakes have emerged as a major concern in today’s digital age. These artificially manipulated videos can be produced with relative ease, and can be used for a variety of purposes, including entertainment, political propaganda, and even fraud. With the rise of deepfakes, there is a growing need for effective detection methods. In this article, we explored the basics of deepfakes, their generation, detection and their impact in the society. This articles also provides an overview of the existing literature on deepfakes and their detection methods. Our analysis suggests that while deepfakes are a significant threat to society, there is need for effective detection and mitigation using advanced forensic techniques. Additionally, the article also spreads awareness about the deepfakes to overcome the chaos that happens due to spreading fake news, revenge porn, manipulating videos and other criminal acts causing harm to individual or organizations reputation.